Methodological approaches for producing doubled haploids in sugar beet and red beet (Beta vulgaris L.) - T. R. Grigolava; A. V. Vishnyakova; A. A. Sinitsyna; A. V. Voronina; O. N. Zubko; O. V. Zudova; S. G. Monakhos (Вавиловский журнал генетики и селекции)
The in vitro production of doubled haploids is a biotechnological path of an accelerated development of parental lines in F1-hybrid breeding programs. Unlike the traditional inbreeding method requiring 5 to 6 generations to reach a sufficient homozygosity of lines, the number of generations to produce pure lines of beet by haploid technologies is reduced to 2. The production of doubled haploids by gynogenesis is the most common biotechnological approach in sugar and red beets. Protocols for the production of doubled haploids for B. vulgaris species are few and have been developed mainly for sugar beets. There are no protocols for the production of doubled haploids for red beet (B. vulgaris convar. esculenta Salisb.), and the protocols developed for sugar beet (B. vulgaris convar. saccharifera Alef.) are ineffective for red beet, even though these two crops belong to the same species. The greatest success has been achieved in the production of doubled haploids by gynogenesis through isolated ovule culture, especially in sugar beet. Studies on the production of doubled haploids by androgenesis were actively carried out in the 1970s and 1980s and did not lead to the production of regenerated plants. However, at present, there is renewed interest among researchers in this approach, and scientists in different countries are conducting studies of Beta vulgaris androgenesis through isolated microspore culture. This article provides an overview of studies devoted to the production of doubled haploids, addressing the main problems of doubled haploid technologies, and methods to increase the frequency of embryogenesis and doubled haploid plant formation in B. vulgaris crops.